The Role of Games and Advantages of Using Games in Learning English - Boboeva Vasila Toshpulatovna, Boboeva Vasila Toshpulatovna, Maxmudova Mavjuda Halimovna, Xasanova Xolida Fattoevna, Ne`matova Moxibehim Fazliddinovna (International Journal of Advanced Science and Technology, 2020)
This article is devoted to the role of games and advantages of using games in learning English.